Antioxidative Responses of Tree Species in Ayer Hitam Forest, Selangor, Peninsular Malaysia - Mohd Fadzillah, Nor'Aini; Ibrahim, Faridah Hanum (Universiti Putra Malaysia Press, 1999)
Antioxidative responses of eight tree species namely Atrocarpus elasticus, Endospermum diadenum, Vitex pinnata, Pellacalyx axillaris, Garcinia atroviridis, Gironniera nervosa, Bouea Oppsitifolia and Callerya atropurpurea were determined from samples collected from both the interior and fringe forest regions of Ayer Hitam Forest Reserve. These antioxidative responses measured include the extent of oxidative deterioration of cellular membrane lipids as well as the concentrations of ascorbate and a-tocopherol, two important endogeneous antioxidants. All eight species showed significant differences in the extent of oxidative deterioration between the interior and fringe forest regions where generally higher levels of membrane lipid peroxidation or oxidative deterioration were observed in samples from the fringe forest regions except for V pinnata and G. nervosa. Concentrations of a-tocopherol were also found to be generally higher in the fringe forest regions except for V.pinnata and G. nervosa. Ascorbate concentrations were however found to be higher in all the tree species sampled from the fringe forest. This thus indicates higher levels of stress conditions with respect to oxidative stress manifested l7y higher levels of disturbance in the fringe forest regions. While G. atropurpurea may represent a good and sensitive indicator species in determining stress conditions in the forest, V pinnata and G. nervosa may represent tree species that are efficient in minimising oxidative deterioration in stress conditions.